Analisis Average Waiting Time Penjadwalan CPU Menggunakan Algoritma Shortest Remaining First dan Algoritma Round Robin - Belferik, Ronald; Banjarnahor, Evander (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
In operating systems, process scheduling is a critical aspect to determine the order of process execution by the CPU. This research compares the average waiting time (AWT) of Shortest Remaining First (SRF) algorithm and Round Robin (RR) algorithm where the problem to be solved is CPU scheduling. The purpose of this research is to get an algorithm that has a short average waiting time. The test results obtained that the SRF algorithm has a very short average waiting time with a value of 29.85 ms compared to the RR algorithm which gets an AWT result of 65.6 ms.